An investigation into the expectations of mothers of children with cochlear implants - Perold, Jennifer Lynne (Division of Communication Sciences and Disorders, 2017)
There is a paucity of research examining the expectations of parents whose children have received a cochlear implant. The process of implantation is fraught with expectations, and in order to ensure continued parental interest and motivation, it is important to have insight into and understanding of these expectations, as well as the factors which influence them. This study aimed to investigate the pre- and post-implant expectations of mothers whose children had received a cochlear implant, as well as the possibility of changes in their expectations with duration of cochlear implant use. It also aimed to examine satisfaction of mothers with the cochlear implant, and the influence this had on expectations. A qualitative research methodology was used in the form of in-depth interviews. Eight mothers of prelingually deafened children who had not yet started formal schooling were interviewed. The data obtained from the mothers was transcribed verbatim and then analysed according to a detailed qualitative analysis procedure. Important findings emerged which detailed the changing expectations based either on hope or knowledge over time. These expectations were influenced by many variables, including the mothers' response to the deafness of the child (i.e. the grief reaction), anxiety and stress, performance outcomes, satisfaction, and expectations of others, including family and friends. Numerous theoretical and clinical implications emerged from these findings, including the dynamic nature of expectations, as well as the impact these have on the importance of ongoing counselling of mothers whose children use cochlear implants.